Medicamentos e corpo: consumidores de fármacos, o que pensam e o que sabem. - Luiz Miguel Santiago; Salvador Massano Cardoso (Acta Médica Portuguesa, 2008)
Little is known about what patients think of the medicines they take. Such knowledge could be of importance for health results. In a primary care setting, the knowledge about pharmacokinetics, pharmacodynamics and about how medicines work in the body were addressed through a validated questionnaire for self fulfillment, in anonymity, to be returned by mail. 272 questionnaires were received representing the population in study in gender and age. As main results knowledge about pharmacokinetics, pharmacodynamics is scarce and there is good knowledge about drug adverse events even though patients don't know how it is medicines work in the body and show very good knowledge about safety medicine's issues. As main conclusions there is little knowledge about how medicines work in the body, much information work being needed to upgrade what patients know in order to ameliorate health results, when medicines are needed.